IoT usage and work-life balance in corporate sector during the COVID-19 pandemic – an exploratory study - Leela Saai, Subramaniam (2022)
The COVID-19 pandemic impacted many industries in Malaysia, particularly the corporate sectors which caused most of the people to exercise social distancing. The impact led many corporate sectors to adopt remote communications for working, socializing, and learning. The government's implementation of new norms as a result of the pandemic has contributed to an alternate way of working life. To support the government's initiative during the pandemic, the transition to remote working was adopted to balance the company and employees' work life. IoT implementation in corporate sectors influences and provides job satisfaction among employees, which in turn influences work-life wellness in the long term. Thus, this study attempted to explore the employee job satisfaction that has a significant relationship with IoT implementation and work-life balance among the residents in Selangor, Putrajaya, and Kuala Lumpur. This study aimed to explore the relationship of two independent variables which are IoT implementation, and work-life balance with the dependent variable of job satisfaction. In addition, two moderating variables of employer management, and family and personal commitments have been further investigated in order to examine their effectiveness in the relationship of both independent variables. This study is interested to understand employee job satisfaction in terms of how worklife balance penetrated the employee personal and professional space to achieve the corporate and personal demands. By using the purposive sampling method, samples of 384 were achieved for quantitative analysis. Data analysis such as correlation, reliability, and descriptive analysis were tested on the samples to further analyse the research objective and hypothesis developed through SPSS 26 Software. As a result, this study concluded that most of the respondents from the corporate sector are currently in a hybrid working mode. Both independent variables of IoT implementation and work-life balance have positive significance towards employee job satisfaction in the corporate industry. The importance of this study, which includes real-world examples of present situations in IoT implementation and work-life balance will aid future presences that may be used to create a better and more digitalized environment.